Trace detection of explosives with a unique large volume injection gas chromatography-mass spectrometry (LVI-GC-MS) method. Issue 23 (4th June 2018) - Marder, Dana; Tzanani, Nitzan; Prihed, Hagit; Gura, Sigalit
Abstract : Highly sensitive splitless programmed temperature vaporizing (PTV)-large volume injection (LVI)-GC-MS-negative chemical ionization (NCI) method was developed and validated for the trace detection of explosives and related compounds from environmental matrices. Abstract : Highly sensitive splitless programmed temperature vaporizing (PTV)-large volume injection (LVI)-GC-MS-negative chemical ionization (NCI) method was developed and validated for the trace detection of explosives and related compounds from environmental matrices. Traditional LVI analysis, whether performed through solvent-vent mode PTV or on-column systems, is characterised by improved detection limits but has limited performance in multi-target and screening applications. Our new approach can reach trace detection levels within a broad range of molecular volatilities (4 orders of magnitude), including volatile compounds, and it represents the first time that this approach has been applied to assess challenging explosive compounds. This is attributed to a unique double-column configuration setup developed for the efficient removal of excess solvent through a flame detector before reaching the MS, with the precise timing of carrier-gas flows and the heating program. The new method simultaneously achieves record-high sensitivities for military and improvised explosives, related by-products and taggants. Detection and quantification limits of 0.1 pg μL −1 (2 pg on column) with a linear dynamic range of at least 2 orders of magnitude, as well as high precision (<20% RSD) and accuracy (<±30%), were determined for most of the compounds. When applying this method to the analysis of spiked soil samples, a detection limit of 0.5 ng g −1 was successfully obtained. This high-performance method may be used for the trace analysis of explosives in real world samples. The principles of the proposed method can be further adjusted to fit other compound families where high sensitivity and broad range of screening are desired.